Differential expression of innate immunity genes in chronic rhinosinusitis - Detwiller, Kara Y. (OceanSide Publications, Inc., 2014)
BACKGROUND: Prior research has identified several components of the innate immune system that may play a significant role in chronic rhinosinusitis (CRS), but the role of innate immunity in patients with CRS is poorly understood. The objective of this study was to determine differential expression of innate immunity genes in the mucosa of patients with CRS with nasal polyposis (CRSwNP) and CRS without nasal polyposis (CRSsNP) when compared with controls. METHODS: Control patients (n = 9) and patients with CRS (n = 36) who failed medical management were prospectively enrolled. Ethmoid mucosa samples were harvested during surgery and quantitative real-time polymerase chain reaction was used to determine levels of mRNA expression of Toll-like receptor (TLR) 2 and TLR9 and interleukin-22 receptor (IL-22R). The average change in crossover threshold and fold change were calculated and differences between controls, CRSwNP, and CRSsNP were compared. Statistical analysis was performed using the Kruskall–Wallis and adjusted Mann–Whitney U tests. RESULTS: Patients with CRSwNP (n = 16) and CRSsNP (n = 20) showed lower mean expression of TLR2 (p < 0.05) compared with controls. Patients with CRSsNP showed significantly higher mean expression of IL-22R (p < 0.05) than controls. CONCLUSION: The sinonasal innate immune system may have a significant role in the development of CRS. We found differential expression of innate immune mediators between patients with and without nasal polyposis. These results provide further evidence of disruption of innate immunity at the mucosal level in CRS and highlight differences between polyp- and non–polyp-forming CRS phenotypes at the molecular level. In addition to our knowledge, this is the first report of altered IL-22R expression in CRSsNP patients. This study was a part of the clinical trial NCT01332136 registered in www.clinicaltrials.gov.